KCNQ2‐DEE: developmental or epileptic encephalopathy?. Issue 3 (22nd February 2021) - Berg, Anne T.; Mahida, Sonal; Poduri, Annapurna
Abstract: Objective: KCNQ2 ‐associated developmental and epileptic encephalopathies (DEE) present with seizures and developmental impairments. The relation between seizures and functional impairments in affected children and the relation of a specific genetic variant to seizure control remains unknown. Methods: Parents of children with documented KCNQ2 variants who participated in a structured, online natural history survey provided information about seizure history, functional mobility, hand use, communication function, and feeding independence. Bivariate analyses were performed with nonparametric methods and logistic regression was used for multivariable analyses. Results: Thirty‐nine children (20, 51% girls, median age 4.5 years, interquartile range (IQR) 1.9—19.3) had a median age of seizure onset of 1 day (IQR 1—3 days). The most common seizure types were bilateral tonic‐clonic ( N = 72, 28%) and bilateral tonic ( N = 13, 33%). Time since last seizure was <6 months ( N = 18, 46%), 6–23 months ( N = 11, 28%), and ≥24 months ( N = 10 26%). Severe functional impairment was reported for mobility (62%), hand grasp (31%), feeding (59%), and communication (77%). Twenty‐eight (72%) were impaired in ≥2 domains. There were only weak and inconsistent associations between seizure recency and individual impairments or number of impairments after adjustment for other factors. The functional location of the variants within the Kv 7.2 protein was not associated with seizure control. Interpretation: Seizures in KCNQ2‐DEE are often well‐controlled, but children have severe impairments regardless. With the increased potential for precision therapies targeting the Kv 7.2 channel or the KCNQ2 gene itself, identifying the most relevant and sensitive clinical endpoints will be critical to ensure successful trials of new therapies.